2013
DOI: 10.1089/ars.2011.4335
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship Between Reactive Oxygen Species and Cyclooxygenase-2 and Vascular Dysfunction in Hypertension

Abstract: The excess of ROS from NAD(P)H Oxidase and/or mitochondria and the increased vascular COX-2/TP receptor axis act in concert to induce vascular dysfunction and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
108
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 37 publications
11
108
0
8
Order By: Relevance
“…AngII treatment increased vasoconstrictor responses to phenylephrine in WT mice, as described, 12 but not in GRK2 +/− mice ( Figure 4A and 4B). Because AngII infusion decreases NO availability in aorta, 12 the lack of effect of AngII on phenylephrine responses in GRK2 +/− arteries might be related to a lesser decrease in NO.…”
Section: Grk2 Deficiency Improves Vascular Function and No Signaling supporting
confidence: 66%
See 1 more Smart Citation
“…AngII treatment increased vasoconstrictor responses to phenylephrine in WT mice, as described, 12 but not in GRK2 +/− mice ( Figure 4A and 4B). Because AngII infusion decreases NO availability in aorta, 12 the lack of effect of AngII on phenylephrine responses in GRK2 +/− arteries might be related to a lesser decrease in NO.…”
Section: Grk2 Deficiency Improves Vascular Function and No Signaling supporting
confidence: 66%
“…Because AngII infusion decreases NO availability in aorta, 12 the lack of effect of AngII on phenylephrine responses in GRK2 +/− arteries might be related to a lesser decrease in NO. As shown in Figure 4C and 4D, the NOS inhibitor N-nitro-l-arginine methyl ester (l-NAME; 100 µmol/L) enhanced phenylephrine contraction in GRK2 +/− aortas more than in WT vessels after AngII (dAUC WT, 59±7; GRK2 +/− , 237±31; P<0.05), suggesting that NO bioavailability after AngII was better preserved in GRK2 +/− aortas.…”
Section: Grk2 Deficiency Improves Vascular Function and No Signaling mentioning
confidence: 99%
“…We also demonstrated the contribution of COX‐2 to BCAA‐induced contraction as the selective COX‐2 inhibitor celecoxib also abolished BCAA contractile responses in L‐NAME‐incubated arteries. Whether this effect was due to COX‐2‐derived prostanoids or to the reciprocal relationship between ROS and COX‐2 suggested previously,51, 52, 53, 54 is unknown. More importantly, our data demonstrate that this excessive O 2 ·− likely reacts with NO leading to increased peroxynitrite formation and nitrosylated proteins, decreased NO availability and in turn, endothelium dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…The reasons for the different contribution of mitochondria and NADPH oxidase to the different parameters are unknown and probably rely on a complex regulation of each response or a possible reciprocal relationship between both sources as described earlier 54, 55. Finally, other sources of O 2 ·− such as the uncoupled eNOS, COX‐2 or xanthine oxidase among others, cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that ROS activate COX, and that COX and its products induce ROS generation. This reciprocal association was mainly identified in hypertensive conditions (123) and in endotoxic shock (197).…”
Section: Other Mechanisms: Testosterone and Ros Generation/oxidative mentioning
confidence: 86%